Changes in the Incidence of Immune Thrombocytopenia in the Coronavirus Disease 2019 Era: A Nationwide Observational Study in Korea - Choi YB; Jung HJ; Kim HR; Jeong SI (Dove Medical Press, 2023)
Young Bae Choi,1,* Hyun Joo Jung,1,* Hae-Rim Kim,2 Soo In Jeong1 1Department of Pediatrics, Ajou University School of Medicine, Ajou University Hospital, Suwon, Korea; 2College of Natural Science, School of Statistics, University of Seoul, Seoul, Korea*These authors contributed equally to this workCorrespondence: Soo In Jeong, Department of Pediatrics, Ajou University School of Medicine, Ajou University Hospital, 164, World Cup-Ro, Yeongtong-Gu, Suwon, 16499, Korea, Tel +82-31-219-5160, Fax +82-31-219-5169, Email sooinjeong@aumc.or.krPurpose: We investigated whether nonpharmaceutical interventions (NPI) to reduce the spread of coronavirus disease 2019 (COVID-19) was associated with a change in the incidence of immune thrombocytopenia (ITP).Patients and Methods: Using the Korean Health Insurance Review and Assessment Services (HIRA) database, individuals newly diagnosed with ITP between January 2015 and December 2020 were identified. The NPI period was defined as February 2020 to December 2020. The ITP incidence in the NPI period was compared with the mean annual incidence during the same months in the pre-NPI period and the incidence predicted by the autoregressive integrated moving average model.Results: In total, 25,723 patients were identified, and the overall annual incidence of ITP was 8.28 per 100,000 persons ([95% confidence interval (CI): 8.18- 8.39]. The ITP incidence in the NPI period was 6.60 per 100,000 person-years (95% CI: 6.37- 6.85), 0.77 times (95% CI: 0.74- 0.80) lower than that during the pre-NPI period [8.62/100,000 (95% CI: 8.50− 8.74)]. With the exception for patients aged ≥ 70 years, the ITP incidence was significantly lower in the NPI period than in the pre-NPI period. The most significant decline in the ITP incidence during the NPI period was observed in the 0- 9 years age group [25.76/100,000 vs 14.01/100,000, P < 0.001; incidence rate ratio (IRR): 0.54 (95% CI: 0.51- 0.58)]. The intravenous immunoglobulin-treated ITP incidence in the NPI period was 1.69/100,000 (95% CI: 1.58- 1.81), 0.79 times (95% CI: 0.73- 0.85) lower than that in the pre-NPI period 2.15/100,000 (95% CI: 2.09− 2.21)]. The incidence of steroid-treated ITP was lower in the NPI period than in the pre-NPI period (2.73/100,000 vs 2.2/100,000, P < 0.001), with an IRR of 0.80 (95% CI: 0.76- 0.83).Conclusion: This nationwide study revealed a significant decrease in ITP incidence, particularly among children, after the implementation of NPI.Keywords: purpura, thrombocytopenic, idiopathic, COVID-19, incidence, pandemic